Implementasi CNN (Convolutional Neural Network) Untuk Mendeteksi Penggunaan Masker Menggunakan Open CV - Muhammad Derio; Hendri Ardiansyah (OKTAL : Jurnal Ilmu Komputer dan Sains, 2024)
The use of technology, especially computer vision, is needed for certain fields. Its wide application can be applied in various fields such as medicine, security, and automotive for automatic control cars. The use of broad computer vision is expected to provide benefits, especially for humans. Face mask detector was developed with the help of the OpenCV library and the CNN method. The first process given is to learn the data model that needs to be leaned through deep learning algorithms. After the data has been trained, the next step is to classify the data based on the division of groups or commonly called sigmoid in deep learning. The final result given is to provide a prediction.